Nanoelectrocatalytic oxidation of lactic acid using nickel nanoparticles - Sedenho, Graziela C. [UNESP]; Lee, Patricia T.; Toh, Her Shuang; Salter, Chris; Johnston, Colin; Stradiotto, Nelson R. [UNESP]; Compton, Richard G. (Amer Chemical Soc, 2015)
We report the electrocatalytic effect of oxidized nickel nanoparticles on lactic acid oxidation in alkaline solution. A boron-doped diamond electrode was modified with nickel nanoparticles by electrodeposition. Various electrodeposition charges were used to deposit nanoparticles of different sizes onto the electrode. Afterward, the nickel nanoparticle modified boron-doped diamond electrodes were initially oxidized in NaOH solution to form beta-Ni(OH)(2) on the surface. Further oxidation forms the Ni(2+/3+) redox couple, beta-Ni(OH)(2)/beta-NiOOH, which catalyzes lactic acid oxidation. Studies in the absence and in the presence of lactic acid were performed and compared to the behavior of the Ni(2+/3+) redox couple on a bulk nickel electrode. The anodic peak was greater than the cathodic peak current in both situations and attributed to the catalytic effect of NiOOH on the oxidation of lactic acid. The ratio between the anodic and cathodic peaks was normalized to the amount of the Ni((2+/3+)) couple on the electrode, and it was found that for suitably small nickel nanoparticles (diameter = 31.8 +/- 7.0 nm) authentic catalytic behavior was seen when compared to a bulk nickel electrode.